The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

The Lesbian and gay studies reader - Abelove, Henry; Barale, Michèle Aina; Halperin, David M. (Routledge, 1993)
Rassemblant quarante-deux essais révolutionnaires, dont beaucoup sont déjà des classiques, The Lesbian and Gay Studies Reader fournit une introduction indispensable à l'état contemporain des études lesbiennes/gay, illustrant largement l'étendue, la portée, la diversité, l'attrait et puissance du travail actuellement réalisé dans le domaine. Présentant des essais d'éminents chercheurs tels que Judith Butler, John D'Emilio, Kobena Mercer, Adrienne Rich, Gayle Rubin et Eve Kosofsky Sedgwick, The Lesbian and Gay Studies Reader explore une multitude d'expériences sexuelles, ethniques, raciales et socio-économiques. . S'étendant sur des disciplines telles que l'histoire, la littérature, la théorie critique, les études culturelles, les études afro-américaines, les études ethniques, la sociologie, l'anthropologie, la psychologie, les classiques et la philosophie, cette anthologie retrace l'inscription des significations sexuelles dans toutes les formes d'expression culturelle. Représentant le meilleur et le plus important travail en langue anglaise dans le domaine, The Lesbian and Gay Studies Reader aborde des sujets tels que les rôles butch-fem, la construction culturelle du genre, le séparatisme lesbien, la théorie féministe, le sida, l'éducation sexuelle sans risque, le colonialisme, le S /M, Oscar Wilde, Gertrude Stein, les livres pour enfants, le nationalisme noir, les films populaires, Susan Sontag, le placard, l'homophobie, Freud, Sappho, les médias, les hijrasde l'Inde, Robert Mapplethorpe, et la politique de représentation. Il contient également un essai bibliographique détaillé qui fournira aux lecteurs un guide inestimable pour des lectures complémentaires. Contributeurs :Henry Abelove, Tomas Almaguer, Ana Maria Alonso, Michele Barale, Judith Butler, Sue-Ellen Case, Danae Clark, Douglas sertissage, Teresa de Lauretis, John D'Emilio, Jonathan Dollimore, Lee Edelman, Marilyn Frye, Charlotte Furth, Marjorie Garber , Stuart Hall, David Halperin, Phillip Brian Harper, Gloria T. Hull, Maria Teresa Koreck, Audre Lorde, Biddy Martin, Deborah E. McDowell, Kobena Mercer, Richard Meyer, DA Miller, Serena Nanda, Esther Newton, Cindy Patton, Adrienne Rich, Gayle Rubin, Joan W. Scott, Daniel L. Selden, Eve Kosofsky Sedgwick, Barbara Smith, Catharine R. Stimpson, Sasha Torres, Martha Vicinus, Simon Watney, Harriet Whitehead, John J. Winkler, Monique Wittig et Yvonne Yarbro -Bejarano
http://bvbr.bib-bvb.de:8991/exlibris/aleph/a23_1/apache_media/DLCIQ4G6YQGKSDIDV2CF3NB8T7FQBI.pdf
Keywords: approches et analyses; corps; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; outils; ouvrages de références; racisme; santé; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; violences

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
https://www.deslibris.ca/ID/412587
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques